How green is a "Green City"? A review of existing indicators and approaches. - Pace, Rocco; Churkina, Galina; Rivera, Manuel (My University, 2016)
More than half of the world s population currently lives in cities and, consequently, urbanization has been among the major drivers of global environmental change. The fast urban growth, likely to result in a share of 75 % of people living in cities by 2050, has resulted in the development of cities which are unfriendly to people as well as to the environment. As a contribution to reverse this trend, various institutions have organized competitions between cities by ranking the degree of their "greenness", based on quantitative and qualitative indicators accessing economic, social and environmental performances. Most of these competitions have only been conducted once and the studies include different cities because their attendance was voluntarily. In this paper we analyze the potential of city rankings to contribute to a positive development of cities. The first part of this paper analyzes and defines the "Green City" concept comparing the definitions in the literature. Three keywords have been identified to characterize a "Green City": the "environmental quality", "human well-being", and the "political and social action" that aims at the first two dimensions. For measuring the greenness of cities, we analyzed the urban indicators of four popular indices, representing 13 categories which were then grouped into the three "Green City" dimensions. Regarding "environmental quality" and "human well-being", quantitative indicators are used, while qualitative indicators seem better suited to define the "societal and political action". By monitoring the quantitative indicators over time, we are also able to assess the "Green City" performances and at the same time verify the effectiveness of" social and political action". Thus, more clarity in the "Green City" definition is achieved, making constant monitoring of cities performances possible. The use of quantitative and multidimensional indicators can be a valuable tool for urban governance and planning.
Keywords: Stadtentwicklungsplanung; Ökosystem; Stadtökologie; Umweltqualität; Indikator; Messung; Green City; Nachhaltige Stadtentwicklung; Soziale Stadtentwicklung; Monitoring